Chapter Fonti e documenti in prospettiva transnazionale. Selezione critica di documenti editi e inediti - Cruciani, Sante (Studi e saggi, 2023)
The section offers a critical selection of documents from a transnational perspective, both published and unpublished, in French, English, Spanish and Italian within a time span from 1988 to 2006. Trentin's writings document not only the breadth and depth of his reflections on the question of rights and solidarity, on Europe and the European social space, the Mediterranean and the Middle East quadrant, but also on issues such as war and peace, inequality and migration that also mark the international dimension of his trade union-political activity.